Three amphi-Atlantic century-scale cold events during the Bølling-Allerød warm period - Yu, Zicheng; Eicher, Ulrich (Géographie physique et Quaternaire, 2001)
AbstractOxygen isotope composition of carbonates in the sediments of Crawford Lake, southern Canada, reveals multiple climatic events during the last deglaciation, including the Bølling warming, intra-Allerød cold period, Younger Dryas, Preboreal Oscillation, and early-Holocene 8.2-ka cooling. Here we present a high-resolution record (~50-yr sampling interval) of oxygen isotopes from this site during the Bølling-Allerød warm period and discuss its significance by comparing it with other records around the North Atlantic. These new data show three century-scale cold events, including the intra-Bølling cold period, Older Dryas, and intra-Allerød cold period. These climatic events correlate well in sequence and relative magnitude with those found in Greenland ice cores, European lacustrine sediments, and Atlantic Ocean sediments. Three similar oscillations in glaciochemical records from GISP2 ice core imply shift in atmospheric circulation patterns. The amphi-Atlantic distribution of these climate events suggests that these events likely originated from the North Atlantic Ocean and that climatic signals were transmitted through the atmosphere.